Analisis Komparatif Kinerja Keuangan PT Unilever Indonesia Tbk Periode 2024-2025: Pendekatan Rasio Keuangan - Saviona Kinanthi Widhitama; Adetia Putri; Khrisna Anggun Yuliana (PT. Karya Inovatif Nusantara, 2026)
This research aims to conduct a comparative analysis of the financial performance of PT Unilever Indonesia Tbk during the 2024–2025 period using a financial ratio approach. The analysis was conducted by measuring liquidity, solvency, activity, and profitability ratios to assess the company’s ability to meet its short-term and long-term obligations, the effectiveness of its asset utilization, and the level of profit generated. Financial data was obtained from the company’s annual reports and published financial statements. The results of the study indicate differences in financial performance between 2024 and 2025, where liquidity ratios improved, solvency ratios remained relatively stable, activity ratios showed greater efficiency, while profitability ratios fluctuated in line with market dynamics and operating costs. These findings provide a comprehensive overview of the company’s financial condition and can serve as a reference for investors, management, and stakeholders in making strategic decisions.